Policing young minds: Education and security policy in British Southeast Asia. Issue 3 (September 2019) - Trisko Darden, Jessica
What factors contributed to the centralization of colonial rule over time? I argue that internal and external threats to the control of territories and populations can lead to the adoption of centralized state institutions, but where institutions already exist centralization may take the form of incremental institutional adaptation rather than wholesale shifts to direct rule. British perceptions of the threat posed by China-driven mobilization amongst overseas Chinese (华侨, huaqiao ) evolved over the course of five decades from an external one based on developments in mainland China to an internal threat to British colonial holdings. In response, British colonial education policy shifted from indirect administration of Chinese Schools to more direct methods of control as a way of mitigating this threat. Evidence from the colonies of Malaya, Sarawak, and Singapore demonstrates that the timing and success of changes in British colonial education policy were influenced by local conditions, including the relative size of local Chinese populations and the strength of organized opposition to British reforms. Both international and domestic security conditions interacted to shape British efforts to control Chinese minorities in colonial Southeast Asia.